Number of inadvertent RNA targets for morpholino knockdown in Danio rerio is largely underestimated: evidence from the study of Ser/Arg-rich splicing factors. Issue 16 (21st July 2017) - Joris, Marine; Schloesser, Marie; Baurain, Denis; Hanikenne, Marc; Muller, Marc; Motte, Patrick
Abstract: Although the involvement of Ser/Arg-rich (SR) proteins in RNA metabolism is well documented, their role in vertebrate development remains elusive. We, therefore, elected to take advantage of the zebrafish model organism to study the SR genes' functions using the splicing morpholino (sMO) microinjection and the programmable site-specific nucleases. Consistent with previous research, we revealed discrepancies between the mutant and morphant phenotypes and we show that these inconsistencies may result from a large number of unsuspected inadvertent morpholino RNA targets. While microinjection of MOs directed against srsf5a (sMO srsf5a ) led to developmental defects, the corresponding homozygous mutants did not display any phenotypic traits. Furthermore, microinjection of sMO srsf5a into srsf5a −/− led to the previously observed morphant phenotype. Similar findings were observed for other SR genes. sMO srsf5a alternative target genes were identified using deep mRNA sequencing. We uncovered that only 11 consecutive bases complementary to sMO srsf5a are sufficient for binding and subsequent blocking of splice sites. In addition, we observed that sMO srsf5a secondary targets can be reduced by increasing embryos growth temperature after microinjection. Our data contribute to the debate about MO specificity, efficacy and the number of unknown targeted sequences.